Teknologi Silase dan Pakan Komplit untuk Meningkatkan Pendapatan Usaha Penggemukan Domba Muda - Hidayati, Asmah; Adiyastiti, Bayu Etti Tri; Ambarwati, Titiek (Universitas Tribhuwana Tunggadewi Malang, 2022)
The young sheep fattening business, which was developed with funding from the PPUPIK Program, was to develop a profit unit and increase the income of the sheep fattening business at the Experimental Farm Laboratory of the UMM Department of Animal Husbandry. In addition, it also fosters a culture of commercialization of research results by lecturers and students and builds cooperation with business actors engaged in sheep breeding. The results of PPUPIK's 2nd year of young lamb fattening have been achieved, namely the cultivation of 151 sheep, with details of 85 sheep cultivated from PPUPIK, consisting of 1 male, 3 broods and 81 enlargements, and 66 heads from UMM. Sales for qurban 48 tails. There is a diversification of sales in the form of carcasses of 5 sheep. Currently available 98 tails, for sale in September to December. To maintain and increase the population, the plan is to purchase 60 cempe starting in October. Silage production reaches 81,000 kg or 81 tons for livestock purposes managed by PPUPIK, and outbound sales only reach 1350 kg, there are problems with raw materials, because the status of an 11 ha land area must be off to support the isolation environment for Covid 19 patients. Sales of pellet concentrate as a substitute for production silage is constrained by raw materials, starting in June as much as 3000 kg. The involvement of students who take part in PPUPIK activities is converted as the value of Animal Husbandry Practices, as many as 3 teams or 9 peopleABSTRAKUsaha penggemukan domba muda yang dikembangkan dengan pendanaan Program PPUPIK ini untuk mengembangkan unit profit dan meningkatkan pendapatan usaha penggemukan domba di Laboratorium Experimental Farm Jurusan Peternakan UMM. Selain itu juga menumbuhkan budaya komersialisasi hasil penelitian dosen maupun mahasiswa dan membangun kerjasama dengan pelaku usaha yang bergerak dalam pembibitan domba. Hasil PPUPIK penggemukan domba muda tahun ke 2 telah dicapai yaitu budidaya domba sejumlah 151 ekor, dengan perincian 85 ekor domba hasil budidaya dari PPUPIK, terdiri dari 1 pejantan, 3 induk dan 81 pembesaran, dan 66 ekor dari UMM. Penjualan untuk qurban 48 ekor. Ada diversifikasi penjualan dalam bentuk karkas sebanyak 5 ekor domba . Saat ini tersedia 98 ekor, untuk penjualan bulan september sampai dengan desember. Untuk mempertahankan dan meningkatkan populasi maka rencana pembelian cempe 60 ekor mulai bulan Oktober. Produksi silase mencapai 81.000 kg atau 81 ton untuk keperluan ternak yang dikelola PPUPIK, dan penjualan keluar hanya mencapai 1350 kg, ada kendala bahan baku, karena status lahan seluas 11 ha harus off untuk mendukung lingkungan isolasi pasien Covid 19. Penjualan konsentrat pellet sebagai pengganti produksi silase yang terkendala bahan baku, mulai Juni sebanyak 3000 kg. Keterlibatan mahasiswa yang ikut dalam kegiatan PPUPIK dikonversi sebagai nilai Praktek usaha Peternakan, sebanyak 3 tim atau 9 orang.